Placental histology, perioperative brain development, and neurodevelopmental outcome at 1 year of age in patients undergoing neonatal cardiac surgery—is there an association? - Steger, Céline; Boegeholz, Alexander; Latal, Beatrice; Feldmann, Maria; Kottke, Raimund; Hagmann, Cornelia; Restin, Tanja; Tuura O'Gorman, Ruth; Jakab, Andras; Reinehr, Michael; Knirsch, Walter (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients with congenital heart disease (CHD) who are operated on after birth are at risk for neurodevelopmental (ND) impairment. Before birth, altered fetal hemodynamics due to the CHD may lead to reduced cerebral perfusion and oxygen supply. The placenta as a critical organ may enhance this pathology.MethodsNeonates with operated complex CHD were included. We scored the placental pathology and analyzed structural and volumetric brain changes of perioperative brain MRI and ND outcome data using the Bayley III at 1 year of age.ResultsA total of 45 (13 female) patients with D-transposition of the great arteries (n = 19, 42.2%), single ventricle CHD (n = 14, 31.1%), left ventricular outflow tract CHD (n = 7, 15.6%), and other (n = 5, 11.1%) were analyzed. Placental findings were abnormal in 21 of 45 patients (46.7%). Pre- and postoperative cMRI were analyzed in 26 (57.8%) and 36 (80%) patients, respectively, while 18 (40%) patients had both (pre-/postoperative) cMRI. Half of our patients had structural brain lesions before (50%) and after (52.8%) surgery, mild intracerebral hemorrhages (pre, 11.1%; post, 22.2%), small cerebral strokes (pre/post, 8.9%), white matter injury (pre/post, 0%/4.5%), and mild hypoxia (pre/post, 4.5%). Abnormal placental findings were not associated with more structural brain lesions but were associated with smaller total brain volumes, cortical gray matter, and cerebellar structures (all p < 0.05), but not with ND outcome at 1 year of age.ConclusionsAbnormal placental findings in patients with complex CHD are associated with smaller brain volumes, underlining the impact of placental function on brain development as a cofactor in patients with CHD.